2020
DOI: 10.1101/2020.09.16.20196154
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 antibody signatures robustly predict diverse antiviral functions relevant for convalescent plasma therapy

Abstract: Convalescent plasma has emerged as a promising COVID-19 treatment. However, the humoral factors that contribute to efficacy are poorly understood. This study functionally and phenotypically profiled plasma from eligible convalescent donors. In addition to viral neutralization, convalescent plasma contained antibodies capable of mediating such Fc-dependent functions as complement activation, phagocytosis and antibody-dependent cellular cytotoxicity against SARS-CoV-2. These activities expand the antiviral funct… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(63 citation statements)
references
References 61 publications
1
62
0
Order By: Relevance
“…(8) We also measured ADCP, ADCC, and ADCD for each plasma donation. (13) We recently used a massively multiplexed For all plasma samples, we measured antibody binding to each 56 amino acid peptide in the library. In each group of samples, we examined two virus-level reactivity scores: (i) aggregate reactivity across all peptides from each virus ( Figure 1B), and (ii) aggregate reactivity across the frequently reactive (dominant) peptides from each virus ( Figure 1C).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…(8) We also measured ADCP, ADCC, and ADCD for each plasma donation. (13) We recently used a massively multiplexed For all plasma samples, we measured antibody binding to each 56 amino acid peptide in the library. In each group of samples, we examined two virus-level reactivity scores: (i) aggregate reactivity across all peptides from each virus ( Figure 1B), and (ii) aggregate reactivity across the frequently reactive (dominant) peptides from each virus ( Figure 1C).…”
Section: Resultsmentioning
confidence: 99%
“…The antibody response to CoV2 is highly variable in terms of titer, (8,9) avidity, (10) antigenic preference, (11,12) kinetics of induction, (9) isotype usage, (13) and functionally protective capacity. (13) Differential pre-existing immune responses to endemic HCoVs may contribute to the large variation in CoV2 antibody response. Recent studies of pre-pandemic plasma identified a low prevalence of pre-existing reactivity against the S2 subunit of the CoV2 spike (S) protein.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fc-mediated effector activity of antibodies has been recently shown to correlate with reduced disease severity and mortality (21). Antibodies capable of mediating Fc-dependant functions, such as antibody-dependent phagocytosis and ADCC, have been isolated from convalescent donors (35). Importantly, Fc-mediated effector activity was shown to protect from SARS-CoV-2 10 infection in adapted mice and hamster models (9,19,32).…”
Section: Discussionmentioning
confidence: 99%